Association of serum uric acid-to-high-density lipoprotein cholesterol ratio with non-alcoholic fatty liver disease in American adults: a population-based analysis - Xie, Yilian; Huang, Kai; Zhang, Xiangyu; Wu, Zhouxiao; Wu, Yiyi; Chu, Jinguo; Kong, Weiliang; Qian, Guoqing (Frontiers in Medicine, 2023)
Objective Non-invasive disease indicators are currently limited and need further research due to the increased non-alcoholic fatty liver disease (NAFLD) prevalence worldwide. The serum uric acid-to-high-density lipoprotein cholesterol ratio (UHR) has been recognized as a novel inflammatory and metabolic marker. Herein, we explored the correlation between UHR and the risk of NAFLD in-depth. Methods A total of 3,766 participants were included in our survey, and the National Health and Nutrition Examination Survey (NHANES) 2017–2018 cycle provided the cross-sectional study population. Weighted multivariable logistic regression and multivariate linear regression analyses were performed to assess the association between the UHR and the odds of NAFLD and liver steatosis and fibrosis severity, respectively. Moreover, we explored the non-linear relationship between the UHR and NAFLD by the generalized additive model. Results NAFLD probabilities were statistically demonstrated to be positively correlated with the UHR (OR = 1.331 per SD increase, 95% CI: 1.100, 1.611). The positive connection of the UHR with NAFLD risk persisted significantly in female subjects but not in male subjects in subgroup analyses stratified by gender. The non-linear relationship analysis demonstrated that a UHR between ~20 and 30% suggested a saturation effect of NAFLD risk. Furthermore, a dramatically positive correlation was found between the UHR and hepatic steatosis severity but not fibrosis. Finally, the receiver operating characteristic analysis suggested that UHR had a better predictive value for NAFLD than either serum uric acid (sUA) or high-density lipoprotein cholesterol (HDL) alone [UHR (area under curve): 0.6910; 95% CI: 0.6737–0.7083; P < 0.0001]. Conclusion Our investigation revealed that the elevated UHR level was independently related to an increased NAFLD risk and the severity of liver steatosis in American individuals. The correlation differed according to sex. This non-invasive indicator may enhance the capacity to predict the onset of NAFLD and may uncover alternative therapeutic interventional targets.